Negative schemata about the self and others and paranoid ideation in at‐risk states and those with persisting positive symptoms. Issue 6 (19th May 2017) - Müller, Hendrik; de Millas, Walter; Gaebel, Wolfgang; Herrlich, Jutta; Hasan, Alkomiet; Janssen, Birgit; Juckel, Georg; Karow, Anne; Kircher, Tilo; Kiszkenow‐Bäker, Stefanie; Klingberg, Stefan; Klosterkötter, Joachim; et al.
Abstract : Background: The objective of this study is to test the conflicting theories concerning the association of negative self and other schemata and paranoid ideation. Methods: A risk‐based approach, including risk stratification, is used to gain insight into the association of the negative self and other schemata that may be shared by individuals or differentiate between individuals at clinical high risk (CHR) for a first‐episode psychosis and those with full‐blown psychosis. The dataset includes a sample of individuals at CHR (n = 137) and a sample of individuals with persisting positive symptoms (PPS, n = 211). The CHR sample was subdivided according to a prognostic index yielding 4 CHR sub‐classes with increasing risk for transition to psychosis. Results: Negative beliefs about the self were associated with paranoid ideation in CHR and a lower risk state. In the highest risk state and full‐blown psychosis, there is an association with negative beliefs about others. Conclusion: These findings are in line with theories suggesting a switch from a predominantly activated negative self‐schema to a malevolent others‐schema in association with paranoid ideation along the risk‐continuum. However, due to methodological limitations these results should be replicated by future studies.